Ethnoracial Populism: An Alternative to Neoliberal Globalization?. (4th July 2019) - Antonio, Robert J.
ABSTRACT: Worldwide emergence of strongmen leaderships and eroded or failed democracies suggest that the era of unchallenged neoliberal hegemony may be winding down and that alternatives are rising. The presidential election of Donald Trump has inspired rightwing populists at home and abroad. This paper will analyze the Trumpist fusion of authoritarian ethnoracial nationalism with neoliberal adventure capitalism and the broader matter of how neoliberal de-democratization opens way for right-wing populism and illiberal capitalism. The topics will be explored in part through discussions of earlier theories of Friedrich Hayek, Carl Schmitt, John Dewey, and Karl Polanyi that have been revived and deployed in the current debates over neoliberalism, populism, and democracy.